2012
DOI: 10.1016/j.scitotenv.2012.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exposure to microbial volatile organic compound and allergy prevalence in single-family homes

Abstract: Microbial volatile organic compounds (MVOCs) are a type of VOCs produced by microorganisms. Exposure to 1-octen-3-ol, one of the known MVOCs, has been reported to reduce nasal patency and increase nasal lavage myeloperoxidase, eosinophil cationic proteins, and lysozymes in both experimental and field studies. We reported in a previous paper that 1-octen-3-ol exposure at home is associated with mucosal symptoms. In this study, our aim was to investigate the relationship between asthma and allergies and MVOC exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 43 publications
0
47
2
2
Order By: Relevance
“…Six studies examined the association between total VOCs and asthma/allergy-related outcomes [36,43,45,46,49,51]. While one cohort study at moderate risk of bias found no associations [36], two case-control studies at moderate risk of bias reported adverse associations between total VOCs and asthma [43,45].…”
Section: Studies Investigating the Role Of Vocs In The Aetiology Of Amentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies examined the association between total VOCs and asthma/allergy-related outcomes [36,43,45,46,49,51]. While one cohort study at moderate risk of bias found no associations [36], two case-control studies at moderate risk of bias reported adverse associations between total VOCs and asthma [43,45].…”
Section: Studies Investigating the Role Of Vocs In The Aetiology Of Amentioning
confidence: 99%
“…Total VOCs were also investigated in one case-control study [46] and two cross-sectional studies [49,51] that were considered to be at high risk of bias (tables S1A and S2).…”
Section: Studies Investigating the Role Of Vocs In The Aetiology Of Amentioning
confidence: 99%
See 3 more Smart Citations